Gender norms in agri-food systems: Value chains - Rietveld, Anne; Morahan, Rebecca; Gallina, Ambra; Iradukunda, Francois; Shijagurumayum, Meghajit (2024)
This annotated bibliography (AB) provides a research overview on the basis of 116 articles. The annotated bibliography was produced to support an evidence synthesis on gender norms in agri-food systems (Rietveld et al., 20231). The aim of the evidence synthesis was to describe how gender norms facilitate, or hamper, women’s abilities to achieve economic resilience in the face of climate change challenges. For each article the title and citation are listed and a description is provided. The description covers the research topic, the methodology, the research findings and conclusions of the article. Sometimes the reviewer has added additional comments. A total of five ABs on ‘gender norms in agri-food systems’ were produced, each focusing on another theme. Next to this AB on ‘Value Chains (#1)’, ABs on ‘Consumer Behaviour’ (#2); Food Environment (#3); Adaptive Behaviour (#4), and Economic Resilience (#5) were produced.